2009
DOI: 10.1128/jb.01715-08
|View full text |Cite
|
Sign up to set email alerts
|

ClpXP Degrades SsrA-Tagged Proteins inStreptococcus pneumoniae

Abstract: Bacterial proteins that are abnormally truncated due to incomplete mRNA or the presence of rare codons are extended by an SsrA tag during ribosome rescue in a trans-translation process important for maintaining protein quality. In Escherichia coli, the SsrA-tagged proteins become the target of the Tsp, Lon, FtsH, ClpXP, and ClpAP proteases. Here we show that degradation of model SsrA-tagged proteins in Streptococcus pneumoniae depends primarily or exclusively on ClpXP in vivo. In addition, we show the E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…2a, b), indicating that ClpP played a core role in the proteolysis of SsrA-tagged proteins. However, we expected that a similar pattern would be observed in the DclpX strain, as ClpA was absent and ClpXP was the only the known proteolytic complex for the degradation of SsrA-tagged proteins in streptococci (Ahlawat & Morrison, 2009). Surprisingly, although significant amounts of GFPssrA and GFPavaa proteins were still present in the DclpX strain, they were drastically reduced (Fig.…”
Section: Ssra-tagged Protein Degradation Does Not Require Adaptors Inmentioning
confidence: 84%
See 4 more Smart Citations
“…2a, b), indicating that ClpP played a core role in the proteolysis of SsrA-tagged proteins. However, we expected that a similar pattern would be observed in the DclpX strain, as ClpA was absent and ClpXP was the only the known proteolytic complex for the degradation of SsrA-tagged proteins in streptococci (Ahlawat & Morrison, 2009). Surprisingly, although significant amounts of GFPssrA and GFPavaa proteins were still present in the DclpX strain, they were drastically reduced (Fig.…”
Section: Ssra-tagged Protein Degradation Does Not Require Adaptors Inmentioning
confidence: 84%
“…ClpXP degrades SsrA-tagged proteins in S. mutans, and the complex formation between ClpX and ClpP is essential for the degradation It was previously reported that ClpXP was responsible for SsrA-tagged protein degradation in Gram-positive bacteria such as B. subtilis and S. pneumoniae (Ahlawat & Morrison, 2009;Wiegert & Schumann, 2001). To determine whether ClpXP also degraded SsrA-tagged proteins in S. mutans, a sequence encoding S. mutans SsrA tag was added to the Cterminal of the GFP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations